To Run or Not to Run? U.S. House Campaign Advertising. Issue 3 (3rd July 2019) - Branton, Regina; Perkins, Jared; Pettey, Samantha
Abstract : Why are campaign advertisements utilized in congressional campaigns? This study examines the factors that influence if and the extent to which campaign ads are sponsored by candidates. Using the 2008 Wisconsin Advertising Project, the 2010 Wesleyan Media Project data sets, and original data on all U.S. House Candidates in the 2008 and 2010 general election, we investigate the candidate- and district-level factors that influence the use of political advertisements. The results indicate the competitiveness of a race, ad costs, heterogeneous media markets, and campaign contributions influence when and the extent to which candidates expend resources on political ads.